NAFTNet retrospective report on the treatment of anti-Ro/SSA mediated fetal heart block with dexamethasone. (12th December 2022) - Sunderji, Sherzana; Peyvandi, Shabnam; Jaeggi, Edgar; Szwast, Anita; Ryan, Greg; Tessier, Francine; Siddiqui, Saad; Cuneo, Bettina; Sheth, Shreya; Treadwell, Marjorie; Frommelt, Michele; Turan, Shifa; et al.
Abstract: Background: Complete atrioventricular block (CAVB) is a complication of maternal antibody positivity and treatment of fetal disease is controversial in terms of efficacy and safety. We hypothesized that dexamethasone treatment for fetal anti-Ro/SSA antibody-mediated cardiac disease leads to better pregnancy outcomes than expectant management. Methods: A retrospective multi-center cohort study of anti-Ro/SSA antibody positive pregnancies with fetal conduction disease reported by participating North American Fetal Therapy Network (NAFTNet) centers between January 2010 and December 2018. The primary outcomes included: fetal death, oligohydramnios, growth restriction, preterm delivery, and new maternal comorbidities. Secondary outcomes included: pacemaker prior to 28 days, transplantation, and neonatal death in maternal/fetal dyads treated with dexamethasone versus not. Results: In 127 anti-Ro/SSA positive pregnancies, 98 were treated with dexamethasone and 29 were not. Of those treated, 61/96 (63.5%) met the primary outcome including 45/91 (49.4%) premature deliveries; 20 mothers developed comorbidities during treatment (fetal death 5, 10 growth restriction, 14 oligohydramnios, two new/worsening gestational diabetes). In the untreated group, 15/25 (60%) met the primary outcome including 11/22 (50%) premature deliveries and four mothers developing comorbidities during their pregnancy (fetal death 3, one growth restriction, one new onset maternal hypertension). Regarding secondary outcomes, 37/96 (43%) treated fetuses required a pacemaker or died by 28 days, while untreated 13/25 (52%) required pacemaker placement, died prior to 28 days or required listing for transplantation. Excluding terminations, survival without transplant was 17 (68%) in untreated and 85 (89%) in treated patients ( p <.01). Conclusions: While the use of dexamethasone in anti-Ro/SSA positive pregnancies is associated with a high rate of poor pregnancy outcomes, there was an unexpected similarly high rate in untreated positive pregnancies. This suggests that the maternal disease itself is influencing pregnancy complications independent of dexamethasone. Our data, which show that treatment decreases neonatal morbidity and overall mortality without increasing overall pregnancy complications, warrant further study.